EBLIDA’s action in Europe - Häggström, Britt Marie (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2004)
EBLIDA is the European Bureau of Library, Information and Documentation Associations. EBLIDA is an independent umbrella association of national library, information, documentation and archive associations and institutions in Europe. EBLIDA was founded in 1992. The initiative to start a new organisation for libraries in Europe came from Germany, UK, Denmark and The Netherlands. Members of EBLIDA are national associations for librarians and archivists. EBLIDA do also have libraries and archives as institutional members.